Analysing the equitable spirit of s 206(3) of the National Land Code 1965 - Mohamad, Nor Asiah (LexisNexis, 2008)
Section 6 of the Civil Law Act 1956 provides for the prohibition of the importation of any part of the British land tenure system into Malaysian land law. The equitableprinciples - originally British - promote justice and fairness with all parties involved in a legal dispute and have been adopted with mixed feelings. The silence of the NLC on the issue of equity and the emphasis on the comprehensiveness of the National Land Code 1965 add more confusion to the polemic. Even though equitable principles can be applied in the Malaysian land system, their application is restricted to what does not undermine the sancity of the National Land Code. This dilemma has prompted several efforts to justify the application of equity, one them being s 206(3) of the National Land Code which allows a more liberal interpretation of equity as legal principle.